2021
DOI: 10.1002/ccd.29738
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with ST‐elevation myocardial infarction and angiographic evidence of coronary artery ectasia

Abstract: Objectives: The aim of this study was to describe the prevalence of coronary artery ectasia (CAE) in patients with ST-elevation myocardial infarction (STEMI) and to compare the long-term outcome of subjects with and without CAE undergoing emergent coronary angiography. Background:The prognostic impact of CAE in STEMI patients has been poorly investigated.Methods: This retrospective, single-center, study included consecutive patients with STEMI undergoing emergent coronary angiography from January 2012 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…However, there are growing evidence that patients with ACS and angiographic evidence of CAE have a high risk of future adverse events at follow up, irrespective of the presence of an EIRA. In a single-center observational study conducted by our group on 534 patients with STEMI, we found that 154 CAE patients developed a higher risk of recurrent MI at longterm follow up compared to a propensity-weighted group of 380 non-CAE STEMI (7). However, no significant differences in allcause death and cardiac death were reported between groups: probably a longer follow up and a larger number of patients might have yielded more conclusive results in terms of long-term mortality.…”
Section: Natural History and Prognostic Stratificationmentioning
confidence: 81%
See 4 more Smart Citations
“…However, there are growing evidence that patients with ACS and angiographic evidence of CAE have a high risk of future adverse events at follow up, irrespective of the presence of an EIRA. In a single-center observational study conducted by our group on 534 patients with STEMI, we found that 154 CAE patients developed a higher risk of recurrent MI at longterm follow up compared to a propensity-weighted group of 380 non-CAE STEMI (7). However, no significant differences in allcause death and cardiac death were reported between groups: probably a longer follow up and a larger number of patients might have yielded more conclusive results in terms of long-term mortality.…”
Section: Natural History and Prognostic Stratificationmentioning
confidence: 81%
“…The wide variability in the reported prevalence has several reasons, including the lack of homogeneity in the adopted definition of CAE, a certain interoperator variability in the angiographic evaluation, geographical discrepancies, and the different clinical presentations of the patients included in the studies. Indeed, an even higher prevalence of CAE was reported in specific clinical settings, reaching up to 9% in some cohorts of patients with STsegment elevation MI (STEMI) (7). Nevertheless, since studies include only patients undergoing coronary angiography and/or presenting with ACS, it is reasonable to think that the real prevalence in the general population may be overestimated.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations